Leveraging Artificial Intelligence in Marketing and Management: A Spatial Analysis of Competitiveness in Muslim Fashion Industry - Yunia Dwie Nurcahyanie; Noerchoidah Noerchoidah; Siti Istikhoroh; Asidigisianti Surya Patria; Sabrina Nur Saraswati (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The Muslim fashion industry in Indonesia is growing rapidly, driven by increasing demand for culturally relevant designs and global market opportunities. This study aims to examine how artificial intelligence enhances the industry’s competitiveness through technology-driven marketing and management strategies, focusing on spatial disparities. A qualitative approach was used, combining interviews with 35 stakeholders in Jakarta, Bandung, and Surabaya, field observations, and spatial analysis using Geographic Information Systems. The findings reveal that urban centres lead in artificial intelligence adoption, achieving 89% accuracy in trend forecasting and a 22% increase in e-commerce conversion rates, while rural areas lag due to limited digital infrastructure. Cultural biases in designs and job displacement are notable challenges. This study is limited to major cities, potentially overlooking rural dynamics. The results highlight the need for inclusive digital policies to bridge the urban-rural gap, ensure culturally sensitive designs, and promote sustainable practices. These strategies can strengthen Indonesia’s position as a global leader in Muslim fashion.